Seed physiology of different crops under the influence of Bt and non-Bt cotton rhizospheric fungi culture filtrate - A.D. Hatti,; A.M. Chavan, P.P. Pangrikar, D.P. Gadgile, (Journal of Phytology, 2009)
Present paper deals with the study of culture filtrate of fungi obtained from rhizosphere of Bt and non-Bt cotton varieties produced by growing these fungi on GN medium and these culture filtrates were tested for seed germination, shoot length and root length of three cereals and three oil seeds. Culture filtrates of fungi isolated from rhizosphere of Bt cotton varieties were found to be more inhibitory for germination of seeds as compared to culture filtrate of fungi isolated from rhizosphere of non Bt-cotton varieties.